Chromosome-Scale Genome and Transcriptomic Analyses Reveal Differential Regulation of Terpenoid Secondary Metabolites in Hericium coralloides - Kexin Meng; Junyi Lv; Tuo Zhang; Yuanyuan Liu; Peng Zhang; Yue Zhang; Banghui Hu; Qianhui Huang; Baogui Xie; Junsheng Fu (Journal of Fungi)
Construction of the genome of Hericium coralloides, a species of edible mushroom, and identification of the genes involved in terpenoid biosynthesis can determine the biology and genetics of terpenoids. The present study describes the assembly of a high-quality chromosome-scale genome of H. coralloides using Pacbio HiFi sequencing and Hi-C technology. This genome consisted of 13 chromosomes, a total size of 43.6 Mb, contigs of N50 3.6 Mb, GC content at 54%, and BUSCOs integrity of 96.9%. Genes associated with terpenoid biosynthesis were predicted by KEGG enrichment analysis and homologous alignment. The Her011461 and Her008335 genes, encoding proteins in the terpenoid backbone synthesis pathway, were found to encode geranylgeranyl pyrophosphate and farnesyl diphosphate synthases, key enzymes in the biosynthesis of geranylgeranyl diphosphate, a precursor of several diterpenoids. Her011463 was found to be involved in regulating diterpene cyclase. The Her005433, Her006724, Her010605, and Her010608 genes were found to encode sesquiterpene synthesis. Most of these genes were more highly expressed in dikaryotic mycelia than in the primordium and fruiting bodies, indicating that terpenoids may be more abundant in dikaryotic mycelia. To our knowledge, this study is the first to assemble the H. coralloides genome at the chromosome scale and to identify the genes involved in terpenoid biosynthesis.